IMPLEMENTATION OF INFAQ SHODAQOH ZAKAT ON MICRO BUSINESS GROWTH AND MUSTAHIQ WELFARE AT LAZISMU SERVICE OFFICE - Eko Susanto; Rahmat Dahlan; Amirudin Amirudin (Universitas Muhammadiyah Prof Dr Hamka, 2023)
This study aims to evaluate the implementation of zakat, infaq, shodaqoh (ZIS) on the growth of micro enterprises and mustahiq welfare at the Lazismu UHAMKA Service Office. This research uses qualitative methods with data collection techniques through interviews and observations. The respondents of the study consisted of mustahiq and the manager of the Lazismu UHAMKA service office. The results showed that the implementation of ZIS had a positive impact on the growth of mustahiq micro-enterprises and their welfare. However, there are still several obstacles in the implementation of the ZIS program, such as the lack of mustahiq awareness in the management of zakat, infaq, and shodaqoh received. Therefore, efforts are needed to increase mustahiq awareness and ZIS program management in order to have a greater impact on mustahiq and the community.